2015
DOI: 10.1002/tie.21695
|View full text |Cite
|
Sign up to set email alerts
|

International Training and Management Development Policies and Practices of South Korean MNEs in China

Abstract: International training and management development has to date received little research attention. This study aims to contribute to the international human resource management literature by empirically exploring international training and management development policies and practices for both expatriates and host‐country nationals (HCNs) of South Korean multinational enterprises (MNEs) operating in China. The data for this study were collected through in‐depth interviews with both HCN managers and expatriate ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 54 publications
(81 reference statements)
2
33
0
1
Order By: Relevance
“…(E4) Finalizando as entrevistas, quando questionados a respeito das competências adquiridas durante o período passado fora do país, grande parte dos entrevistados salientou a importância do programa para aprimorar a comunicação e o trabalho em equipe envolvendo pessoas de culturas diferentes, desenvolver conhecimento mais técnico relacionado ao trabalho e realizar benchmarking. Analisando os benefícios elencados, verifica-se que vêm ao encontro do que constataram Kang, Shen, Xu (2015) em seu estudo a respeito das vantagens dos treinamentos realizados internacionalmente, que não se limitam ao desenvolvimento de competências técnicas, à medida que os profissionais que vivenciam uma experiência em outro país tendem a desenvolver também competências interpessoais.…”
Section: Apresentação E Discussão De Resultadosunclassified
“…(E4) Finalizando as entrevistas, quando questionados a respeito das competências adquiridas durante o período passado fora do país, grande parte dos entrevistados salientou a importância do programa para aprimorar a comunicação e o trabalho em equipe envolvendo pessoas de culturas diferentes, desenvolver conhecimento mais técnico relacionado ao trabalho e realizar benchmarking. Analisando os benefícios elencados, verifica-se que vêm ao encontro do que constataram Kang, Shen, Xu (2015) em seu estudo a respeito das vantagens dos treinamentos realizados internacionalmente, que não se limitam ao desenvolvimento de competências técnicas, à medida que os profissionais que vivenciam uma experiência em outro país tendem a desenvolver também competências interpessoais.…”
Section: Apresentação E Discussão De Resultadosunclassified
“…Review results demonstrate that 25 articles from the selection focused on internal factors of the employees (Table 1). Satisfaction (King et al, 2012;Saira et al, 2020;Thakur et al, 2016;Waight & Madera, 2011;Yap et al, 2010), commitment (Kang et al, 2015;Saira et al, 2020;Thakur et al, 2016;Yap et al, 2010), and cultural quotient (CQ; Kamal Abdien & Jacob, 2019; Kotsaga, 2015;MacNab, 2012;Rehg et al, 2012) (Ehrke et al, 2014) and inclusion values of the organization (Noon & Ogbonna, 2021), prejudices and internal motivation of the employees (Lindsey et al, 2015), confidence, and comfort of working with LGBTQ individuals (Israel et al, 2014), the turnover intention of minority employees (Waight & Madera, 2011), and intercultural relationships in the virtual teams (Sanchez-Burks et al, 2007).…”
Section: Dominance Of Internal Factorsmentioning
confidence: 99%
“…Commitment (Kang et al, 2015;Saira et al, 2020;Thakur et al, 2016;Yap et al, 2010) Previous research has demonstrated that employee satisfaction and commitment are critically reflected in their interaction with consumers (Agyeiwaah et al, 2021;Brown & Lam, 2008;Jeon & Choi, 2012;Scotti et al, 2003). Furthermore, research has also established that employees' diversity intelligence (measured by CQ) impacts consumer interaction and satisfaction (Gaur et al, 2017;Netemeyer et al, 2010).…”
Section: Dominance Of Internal Factorsmentioning
confidence: 99%
“…The second category of expatriate literature features analyses of language-sensitive institutional HR practices and falls within the structural dimension of global work. While some scholars have found some MNCs to include language classes in pre-departure cross-cultural training (CCT) (Kang and Shen, 2014; Kang et al , 2015; Tung, 1982) and supported the potential positive effects (Bhatti et al , 2013; Dowling et al , 2013; Suutari and Brewster, 1998; Wang and Tran, 2012) on CCA dimensions (Wang and Tran, 2012) or performance (Ko and Yang, 2011), the empirical results of CCT effectiveness are mixed (Puck et al , 2008; Wurtz, 2014). Scholars have argued that the variation between expatriate profiles, assignment destinations and tasks require differentiated training, also in terms of language (Potter and Richardson, 2019).…”
Section: Language In Expatriate Researchmentioning
confidence: 99%